Battery diaphragm and battery
By introducing N elements into polymer particles and optimizing their composition, the problem of poor affinity of polymer particles for electrolyte is solved, the electrolyte wetting and heat resistance of lithium battery separators is improved, and the lithium battery manufacturing process is improved liquid injection efficiency.
Patent Information
- Application Number
- CN202411817495.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-12-11
AI Technical Summary
In the prior art, the polymer particles have poor affinity for the electrolyte, resulting in poor wetting of the electrolyte of the lithium battery separator and affecting the liquid injection efficiency during the lithium battery manufacturing process.
Introduce N elements into polymer particles, control the mass ratio of N elements to C elements to be (2-10):100, and rigid ring structural units, crosslinked monomer units and functional monomer units are added to the heat-resistant layer. , optimize the particle size and glass transition temperature of polymer particles to improve the electrolyte wetting and the heat resistance of the membrane.
It significantly improves the electrolyte wetting of polymer particles, improves the liquid injection efficiency during lithium battery manufacturing, and maintains the heat resistance and breathability of the diaphragm.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of battery materials, and in particular relates to a battery separator and a battery. Background Art
[0002] Boehmite (γ-AlOOH) first loses physically adsorbed water under heat, and as the temperature rises, it begins to lose chemically adsorbed water when the temperature reaches 210°C, and completely loses all water at 310°C. Due to its excellent heat resistance and good chemical stability, it is mainly used for coating lithium battery cell separators. Moreover, boehmite expands when heated, and this expansion is mainly manifested as changes in lattice parameters and structural reorganization. This expansion characteristic enables boehmite to have certain protective functions in high temperature environments, such as preventing overcharging and explosion through closed-cell functions in the application of lithium battery separators. Specifically: at lower temperatures (e.g., below 300°C), the structural changes of boehmite are mainly manifested as water loss and increased density. When the temperature rises to about 300°C, cracks and fissures begin to appear in boehmite, indicating that its thermal expansion begins to increase significantly. At higher temperatures (e.g., above 400°C), the thermal expansion of boehmite leads to grain coarsening and increased pores, further increasing the thermal expansion rate. When the temperature continues to rise to above 700°C, boehmite undergoes size sintering, resulting in further coarsening of crystals and pores and a continued increase in thermal expansion rate.
[0003] During the use of boehmite, additional dispersing equipment is usually required for dispersion. Due to the irregular morphology of boehmite particles, friction with the equipment is inevitable during the dispersion process, causing equipment wear, and metal impurities will be introduced into the boehmite slurry, which will have a negative impact on battery performance.
[0004] In order to overcome the above problems, polymer particles are used in the prior art to replace boehmite as the main filler of the heat-resistant layer of the battery separator. However, the polymer particles in the prior art have poor affinity for the electrolyte, and the polymer coating coated with the polymer particles usually has poor electrolyte wettability. Summary of the invention
[0005] In view of the technical problems in the prior art that the polymer particles have poor affinity for the electrolyte and the diaphragm has poor electrolyte wettability, the specific technical solution of this application is as follows: A battery separator comprises a base film layer and a heat-resistant layer arranged on at least one side of the base film layer, wherein the heat-resistant layer comprises polymer particles; the mass ratio of the N element content to the C element content in the polymer particles is (2-10):100.
[0006] The present application introduces N element into polymer particles and controls the mass ratio of N element content to C element content to be (2-10):100. On the basis of maintaining the heat resistance and air permeability of the polymer particle separator, the electrolyte wettability of the polymer particles can be significantly improved, which is beneficial to improving the injection efficiency in the lithium battery manufacturing process.
[0007] Preferably, the average particle size D50 of the polymer particles is 200-1000 nm, and the glass transition temperature Tg is above 150°C.
[0008] Preferably, the polymer particles include rigid cyclic structural units, cross-linked monomer units and functional monomer units; in the polymer particles, the mass ratio of the rigid cyclic structural units, the cross-linked monomer units and the functional monomer units is (60-90): (5-15): (5-25).
[0009] Preferably, the rigid cyclic structural unit is selected from one or more of aromatic vinyl compound monomer units, maleimide and its derivative monomer units, and vinyl carbazole compound monomer units; the cross-linking monomer unit is selected from one or more of difunctional or multifunctional (meth)acrylate monomer units, difunctional or multifunctional allyl monomer units, difunctional or multifunctional acrylamide monomer units, and difunctional or multifunctional vinyl monomer units; and the functional monomer unit is selected from one or more of amino-containing monomer units.
[0010] Preferably, the rigid cyclic structural unit is selected from one or more of styrene monomer units, methylstyrene monomer units, vinylnaphthalene monomer units, vinyltoluene monomer units, 2,4-dimethylstyrene monomer units, ethylstyrene monomer units, isopropylstyrene monomer units, tert-butylstyrene monomer units, butylstyrene monomer units, phenylstyrene monomer units, cyclohexylstyrene monomer units, benzylstyrene monomer units, isobornyl acrylate monomer units, isobornyl methacrylate monomer units, maleimide monomer units, C1-C12 alkyl-substituted maleimide monomer units, C6-C16 aryl-substituted maleimide monomer units, and vinylcarbazole; The cross-linking monomer unit is selected from the group consisting of ethylene glycol diacrylate monomer unit, polyethylene glycol diacrylate monomer unit, propylene glycol diacrylate monomer unit, dipropylene glycol diacrylate monomer unit, tripropylene glycol diacrylate monomer unit, trimethylolpropane triacrylate monomer unit, glycerol triacrylate monomer unit, pentaerythritol triacrylate monomer unit, polyethylene glycol dimethacrylate monomer unit, diethylene glycol dimethacrylate monomer unit, propylene glycol dimethacrylate monomer unit, dipropylene glycol dimethacrylate monomer unit, tripropylene glycol dimethacrylate monomer unit, One or more of the following monomer units: trimethylolpropane trimethacrylate monomer unit, trimethylolpropane trimethacrylate monomer unit, glycerol trimethacrylate monomer unit, pentaerythritol trimethacrylate monomer unit, divinylbenzene monomer unit, diallyl phthalate monomer unit, glycerol diallyl ether monomer unit, pentaerythritol diallyl ether monomer unit, pentaerythritol triallyl ether monomer unit, diallyl adipate monomer unit, N,N-methylenebisacrylamide monomer unit, acrylic acid allyl ether monomer unit, methacrylic acid allyl ether monomer unit, and divinylbenzene monomer unit; The functional monomer unit is selected from one or more of N-(2-aminoethyl)acrylamide monomer unit, N-(2-aminoethyl)methacrylamide monomer unit, N-(2-aminohexyl)acrylamide monomer unit, N-(2-aminohexyl)acrylamide monomer unit, 2-(tert-butylamino)ethyl methacrylate monomer unit, dimethylaminoethyl acrylate monomer unit, dimethylaminoethyl methacrylate monomer unit, acrylamide monomer unit, methacrylamide monomer unit, N-tert-butylacrylamide monomer unit, N-isopropylacrylamide monomer unit, N,N-dimethylacrylamide monomer unit, and N,N-diethylacrylamide monomer unit.
[0011] Preferably, the thickness of the heat-resistant layer is 1-4 μm.
[0012] Preferably, the heat-resistant layer further comprises a binder and optionally a thickener and a wetting agent.
[0013] Preferably, in the heat-resistant layer, the mass ratio of polymer particles, binder, thickener and wetting agent is 100:(3-10):(0.5-5):(0.5-3).
[0014] Preferably, the base film layer is a polyolefin base film, and the polyolefin base film is selected from any one of a polyethylene porous film, a polypropylene porous film, a polypropylene / polyethylene / polypropylene three-layer composite porous film, and a polybutylene porous film.
[0015] Meanwhile, the present invention also provides a battery, comprising the battery separator as described above. DETAILED DESCRIPTION
[0016] The present application is further described below in conjunction with examples. It should be understood that the examples are only used to further describe and illustrate the present application and are not used to limit the present application.
[0017] Unless otherwise defined, the technical and scientific terms in this specification have the same meaning as those generally understood by those skilled in the art. Although similar or identical methods and materials as described herein may be used in experiments or practical applications, materials and methods are described herein below. In the event of a conflict, the present specification including the definitions therein shall prevail. In addition, materials, methods and examples are provided for illustration only and are not restrictive. The present application is further described below in conjunction with specific embodiments, but is not intended to limit the scope of the present application.
[0018] The battery separator provided by the present invention comprises a base film layer and a heat-resistant layer arranged on at least one side of the base film layer, wherein the heat-resistant layer comprises polymer particles; the mass ratio of the N element content to the C element content in the polymer particles is (2-10):100.
[0019] In a specific embodiment, the mass ratio of the N element content to the C element content in the polymer particles is (2-10): 100. For example, it can be 2:100, 3:100, 4:100, 5:100, 6:100, 7:100, 8:100, 9:100, 10:100.
[0020] When the mass ratio of N to C is lower than 2:100, the polymer particles have insufficient affinity for the electrolyte and the improvement effect on the wettability of the electrolyte is not obvious. When the mass ratio of N to C is higher than 10:100, the porosity of the diaphragm will deteriorate after coating, the air permeability will decrease, and the dispersibility of the polymer particles will deteriorate, making the preparation process more difficult.
[0021] For the above polymer particles, preferably, the average particle size D50 of the polymer particles is 200-1000 nm. Specifically, the average particle size D50 of the polymer particles can be 200 nm, 250 nm, 300 nm, 350 nm, 400 nm, 450 nm, 500 nm, 550 nm, 600 nm, 650 nm, 700 nm, 750 nm, 800 nm, 850 nm, 900 nm, 950 nm, or 1000 nm.
[0022] If the polymer particle size is too small, it is easy to cause the coated diaphragm to have too much air permeability increase, which cannot meet the use requirements of lithium batteries. If the polymer particle size is too large, it is easy to cause insufficient coating layers, resulting in poor heat resistance of the diaphragm.
[0023] According to the present invention, preferably, the glass transition temperature Tg of the polymer particles is above 150° C. More preferably, the glass transition temperature Tg of the polymer particles is 150-500° C. Specifically, the glass transition temperature Tg of the polymer particles may be 150° C., 200° C., 250° C., 300° C., 350° C., 400° C., 450° C., 500° C. If the glass transition temperature Tg of the polymer particles is less than 150° C., the performance of suppressing thermal shrinkage of the separator will decrease.
[0024] In the present invention, the polymer particles can be various types of polymer particles commonly used in the art, and it is only necessary to control the mass ratio of the N and C elements within the range disclosed in the present invention. Preferably, the polymer particles include rigid cyclic structural units, cross-linked monomer units and functional monomer units. More preferably, in the polymer particles, the mass ratio of the rigid cyclic structural units, the cross-linked monomer units and the functional monomer units is (60-90): (5-15): (5-25).
[0025] The rigid cyclic structural unit is a unit formed in a polymer after polymerization of a monomer having a rigid group. Specifically, the rigid cyclic structural unit is selected from one or more of an aromatic vinyl compound monomer unit, a maleimide and its derivative monomer unit, and a vinyl carbazole compound monomer unit. Further, the rigid cyclic structural unit is selected from one or more of a styrene monomer unit, a methyl styrene monomer unit, a vinyl naphthalene monomer unit, a vinyl toluene monomer unit, a 2,4-dimethyl styrene monomer unit, an ethyl styrene monomer unit, an isopropyl styrene monomer unit, a tert-butyl styrene monomer unit, a butyl styrene monomer unit, a phenyl styrene monomer unit, a cyclohexyl styrene monomer unit, a benzyl styrene monomer unit, an isobornyl acrylate monomer unit, an isobornyl methacrylate monomer unit, a maleimide monomer unit, a C1-C12 alkyl substituted maleimide monomer unit, and a C6-C16 aryl substituted maleimide monomer unit.
[0026] The cross-linking monomer unit is a unit formed in the polymer after the cross-linking monomer is polymerized. Specifically, the cross-linking monomer unit is selected from one or more of a difunctional or multifunctional (meth)acrylate monomer unit, a difunctional or multifunctional allyl monomer unit, a difunctional or multifunctional acrylamide monomer unit, and a difunctional or multifunctional vinyl monomer unit; the functional monomer unit is selected from one or more of an amine-containing monomer unit.
[0027] Specifically, the cross-linking monomer unit is selected from ethylene glycol diacrylate monomer unit, polyethylene glycol diacrylate monomer unit, propylene glycol diacrylate monomer unit, dipropylene glycol diacrylate monomer unit, tripropylene glycol diacrylate monomer unit, trimethylolpropane triacrylate monomer unit, glycerol triacrylate monomer unit, pentaerythritol triacrylate monomer unit, polyethylene glycol dimethacrylate monomer unit, diethylene glycol dimethacrylate monomer unit, propylene glycol dimethacrylate monomer unit, dipropylene glycol dimeth ... One or more of dimethacrylate monomer units, trimethylolpropane trimethacrylate monomer units, glycerol trimethacrylate monomer units, pentaerythritol trimethacrylate monomer units, divinylbenzene monomer units, diallyl phthalate monomer units, glycerol diallyl ether monomer units, pentaerythritol diallyl ether monomer units, pentaerythritol triallyl ether monomer units, diallyl adipate monomer units, N,N-methylenebisacrylamide monomer units, allyl acrylic acid ether monomer units, allyl methacrylate monomer units, and divinylbenzene monomer units.
[0028] The functional monomer unit is a unit formed in a polymer after the functional monomer is polymerized. Specifically, the functional monomer unit is selected from one or more of N-(2-aminoethyl)acrylamide monomer unit, N-(2-aminoethyl)methacrylamide monomer unit, N-(2-aminohexyl)acrylamide monomer unit, N-(2-aminohexyl)acrylamide monomer unit, 2-(tert-butylamino)ethyl methacrylate monomer unit, dimethylaminoethyl acrylate monomer unit, dimethylaminoethyl methacrylate monomer unit, acrylamide monomer unit, methacrylamide monomer unit, N-tert-butylacrylamide monomer unit, N-isopropylacrylamide monomer unit, N,N-dimethylacrylamide monomer unit, and N,N-diethylacrylamide monomer unit.
[0029] The functional monomer contains N element. After the N element is introduced into the polymer particles, the electrolyte wettability of the polymer particles can be significantly improved. This may be because the introduction of the N element can effectively improve the polarity of the polymer particles and increase the affinity with the electrolyte. In addition, the N element has good adsorption to the lithium salt in the electrolyte. After the lithium salt is adsorbed on the polymer particles containing the N element, it is further conducive to the infiltration of the electrolyte.
[0030] In the present invention, the mass ratio of the rigid cyclic structural unit, the cross-linking monomer unit and the functional monomer unit in the polymer particles can be based on the mass ratio of the monomer with a rigid group, the cross-linking monomer and the functional monomer participating in the polymerization reaction, that is, the mass ratio of the monomer with a rigid group, the cross-linking monomer and the functional monomer used for polymerization to form polymer particles is (60-90): (5-15): (5-25).
[0031] The polymer particles provided by the present invention can be prepared by a method commonly used in the field of chemical synthesis, for example, 0.1-1 parts of an emulsifier, 50-300 parts of a solvent, and 100 parts of a monomer mixture are mixed and stirred at high speed to obtain a monomer emulsion. Then, nitrogen is introduced and the temperature is raised to 60-100° C., and then an initiator is added. After the reaction is kept warm for 4-10 hours, a dispersion of polymer particles can be obtained.
[0032] It is well known to those skilled in the art that the particle size of polymer particles can be adjusted by adjusting the amount of emulsifier used.
[0033] Among them, the emulsifier can be various conventional substances, and the emulsifier can be an anionic emulsifier, a nonionic emulsifier or a combination of the two, including but not limited to sodium lauryl sulfate, sodium lauryl ether sulfate, and fatty alcohol polyoxyethylene ether. The initiator is usually a water-soluble initiator, including but not limited to sodium persulfate, ammonium persulfate, potassium persulfate, and hydrogen peroxide. The solvent can be deionized water. The monomer mixture is a mixture of monomers with rigid groups, cross-linking monomers, and functional monomers as described above.
[0034] In the present invention, preferably, the thickness of the heat-resistant layer is 1-4 μm.
[0035] If the thickness of the heat-resistant layer is too thin, the heat resistance of the separator will be poor, while if the thickness of the heat-resistant layer is too thick, the air permeability of the separator will be poor and the internal resistance of the battery will increase.
[0036] Furthermore, the heat-resistant layer also includes a binder and optionally a thickener and a wetting agent.
[0037] The binder, thickener and wetting agent can be various materials commonly used in the art. For example, the binder can be a polyacrylate binder and / or a styrene-butadiene latex binder. The polyacrylate binder is commercially available and is in the form of an emulsion with a solid content of 45%, an average particle size D50 of 350-400 nm, and a glass transition temperature of -40°C.
[0038] The thickener may be at least one of sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, sodium polyacrylate, and lithium polyacrylate.
[0039] The wetting agent may be any of various existing wetting agents, for example, any one of alkylphenol polyoxyethylene ether, fatty alcohol polyoxyethylene ether, fatty acid polyoxyethylene ether and polyether-modified polysiloxane or a mixture of several of them.
[0040] Preferably, in the heat-resistant layer, the mass ratio of polymer particles, binder, thickener and wetting agent is 100:(3-10):(0.5-5):(0.5-3).
[0041] In a specific embodiment, the content of the binder is 3-10 parts, for example, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, and 10 parts.
[0042] In a specific embodiment, the thickener is 3-10 parts, for example, 0.5 parts, 1 parts, 2 parts, 3 parts, 4 parts, 5 parts.
[0043] In a specific embodiment, the content of the wetting agent is 0.5-3 parts, for example, it can be: 0.3 parts, 0.5 parts, 0.8 parts, 1 parts, 1.3 parts, 1.5 parts, 1.8 parts, 2 parts, 2.3 parts, 2.5 parts, 2.8 parts, 3 parts.
[0044] Preferably, the base film layer is a polyolefin base film, and the polyolefin base film is selected from any one of a polyethylene porous film, a polypropylene porous film, a polypropylene / polyethylene / polypropylene three-layer composite porous film, and a polybutylene porous film.
[0045] The battery separator provided by the present invention can be obtained by coating a slurry containing polymer particles on a base film layer and then drying the slurry.
[0046] The slurry may include the following components in weight fractions (converted to solid content): polymer particles, binder, thickener, wetting agent in a mass ratio of 100: (3-10): (0.5-5): (0.5-3). The solid content may be adjusted to 30-40 wt% by using a solvent (such as deionized water).
[0047] Meanwhile, the present invention also provides a battery, comprising the battery separator as described above.
[0048] The battery separator provided by the invention has good wettability to electrolyte and low thermal shrinkage.
[0049] Example The following specific examples are used to explain and illustrate the embodiments of the present application in detail, but the following content should not be construed as limiting the present application in any way. The substances used in the examples are all commercially available products unless otherwise specified. The "parts" in the examples and comparative examples all represent kg, and the composition ratios are all weight ratios.
[0050] Example 1 0.5 parts of sodium dodecyl sulfate, 150 parts of water, and 100 parts of monomer mixture were stirred at high speed to obtain a monomer emulsion. After nitrogen was passed and the temperature was raised to 80°C, 0.5 parts of initiator ammonium persulfate were added, and the reaction was kept warm for 6 hours to obtain a polymer particle dispersion. The average particle size D50 of the polymer particles was 450nm as measured by a laser particle size analyzer. The Tg of the polymer particles was 158°C as measured by a differential scanning calorimeter.
[0051] The monomer mixture is composed of styrene:vinyl carbazole:divinylbenzene:N-tert-butyl acrylamide=40:25:10:25.
[0052] Preparation of the diaphragm with a heat-resistant layer: 250 parts of polymer particle dispersion (containing 100 parts of polymer particles), 13.3 parts of polyacrylate binder (solid content of 45%), 1 part of sodium carboxymethyl cellulose, 0.5 parts of alkylphenol polyoxyethylene ether, add deionized water to adjust the solid content to 35%, and obtain a polymer particle slurry. The slurry is coated on the polyethylene base film layer, and the coating thickness after drying is controlled to be 2μm.
[0053] Example 2 The difference between this embodiment and embodiment 1 is that the monomer mixture composition is styrene:vinyl carbazole:divinyl benzene:acrylamide=40:25:10:25.
[0054] The Tg of the polymer particles measured by differential scanning calorimetry was 169°C.
[0055] Example 3
[0056] The difference between this embodiment and embodiment 1 is that the monomer mixture consists of isobornyl methacrylate: vinyl carbazole: divinylbenzene: acrylamide=30:30:15:25.
[0057] The Tg of the polymer particles measured by differential scanning calorimetry was 185°C.
[0058] Example 4
[0059] The difference between this embodiment and embodiment 1 is that the monomer mixture consists of styrene:vinyl carbazole:divinylbenzene:N-tert-butylacrylamide=70:20:5:5.
[0060] The Tg of the polymer particles measured by differential scanning calorimetry was 152°C.
[0061] Example 5
[0062] The only difference between this embodiment and embodiment 1 is that the particle size of the polymer particles is 210 nm.
[0063] Example 6
[0064] The only difference between this embodiment and embodiment 1 is that the particle diameter of the polymer particles is 810 nm.
[0065] Example 7
[0066] The only difference between this embodiment and embodiment 1 is that the particle size of the polymer particles is 970 nm.
[0067] Example 8
[0068] The only difference between this embodiment and embodiment 1 is that the thickness of the polymer particle coating is 1 μm.
[0069] Example 9
[0070] The only difference between this embodiment and embodiment 1 is that the thickness of the polymer particle coating is 4 μm.
[0071] Example 10
[0072] The only difference between this comparative example and Example 2 is that the thickness of the heat-resistant layer is 0.5 μm.
[0073] Embodiment 11
[0074] The only difference between this comparative example and Example 2 is that the thickness of the heat-resistant layer is 5 μm.
[0075] Example 12
[0076] The difference between this comparative example and Example 2 is that the monomer mixture composition is styrene:vinyl carbazole:divinylbenzene:N-tert-butylacrylamide=90:10:5:5.
[0077] The Tg of the polymer particles measured by differential scanning calorimetry was 131°C.
[0078] Comparative Example 1 The difference between this comparative example and Example 2 is that the monomer mixture composition is styrene:vinyl carbazole:divinyl benzene=70:20:10.
[0079] Comparative Example 2 The difference between this comparative example and Example 2 is that the monomer mixture composition is styrene:vinyl carbazole:divinylbenzene:acrylamide=35:20:10:35.
[0080] Comparative Example 3 The difference between this comparative example and Example 2 is that boehmite BG-611 is used to replace the polymer particles.
[0081] Performance test: Diaphragm air permeability value-added test, refer to the air permeability test in GB / T 36363-2018 "Polyolefin diaphragm for lithium-ion batteries": Cut three pieces of diaphragm from the film roll at 150mm intervals in the longitudinal direction. If the diaphragm width is ≥100mm, the sample size is 100mm×100mm. If the diaphragm width is <100mm, the sample size is 100mm×diaphragm width. Place the diaphragm in the test head of the permeability meter suitable for the test range for permeability time test. Take the average value of the three test results as the permeability time of the diaphragm, in s / 100cc. The permeability value of the diaphragm is the difference between the permeability time of the diaphragm coated with non-conductive particles and adhesives and the permeability time of the diaphragm of the polyolefin base film, in s / 100cc.
[0082] The contents of C and N elements were detected by elemental analysis, and the N / C ratio was the N content divided by the C content.
[0083] Electrolyte wettability test: Cut the diaphragm coated with polymer particles into 5mm*100mm strips, add 3μL of electrolyte to the diaphragm strips, and test the length of electrolyte diffusion after 1 minute. The unit is mm. The electrolyte composition is ethylene carbonate: ethyl methyl carbonate: diethyl carbonate = 3:2:5, and the concentration of lithium hexafluorophosphate is 1 mol / L.
[0084] Heat resistance of diaphragm: stack the diaphragm into 3 layers, exhaust the air between the membranes, take out the sample cut into 100 mm*100 mm, measure the longitudinal length M1 and transverse length T1 of the cut sample, set the oven temperature to 130℃, keep it warm for 1 hour after the temperature is reached, put the sample in the oven and keep it warm for 1 hour. After the insulation is completed, take out the diaphragm, cool it for 10 minutes, and then measure the longitudinal length M2 and transverse length T2 of the sample. The longitudinal heat shrinkage of the diaphragm = (M1-M2) / M1*100%, and the transverse heat shrinkage = (T1-T2) / T1*100%.
[0085] Glass transition temperature test: The glass transition temperatures of the core polymer and the shell polymer were tested using a differential scanning calorimeter (Shanghai Qunhong Instrument Equipment Co., Ltd., model: DSC-100).
[0086] The above test results are filled in Table 1.
[0087] Table 1
[0088] It can be seen from the test results in Table 1 that the battery separator provided by the present invention has good electrolyte wettability, and at the same time has low air permeability and low thermal shrinkage.
[0089] By comparing the test results of Example 2 and Comparative Examples 1 and 2, it can be seen that when the mass ratio of N element to C element is too low, the electrolyte wettability of the battery separator is significantly reduced, while when the mass ratio of the two is too high, the air permeability value of the battery separator is significantly increased.
[0090] By comparing the test results of Examples 1, 5, 6 and 7, it can be seen that when the average particle size D50 of the polymer particles is low, the air permeability value of the battery separator tends to increase.
[0091] Comparing the test results of Examples 2 and 12, it can be seen that when the glass transition temperature Tg of the polymer particles is reduced, it is not beneficial to suppress the thermal shrinkage of the separator.
[0092] The above is only the preferred experimental example of the present application, and does not limit the present application in other forms. Any technician familiar with the profession may use the technical content disclosed above to change or modify it into an equivalent experimental example with equivalent changes. However, any simple modification, equivalent change and modification made to the above experimental examples based on the technical essence of the present application without departing from the content of the technical solution of the present application still falls within the protection scope of the technical solution of the present application.
Claims
1. A battery separator, characterized in that: It comprises a base film layer and a heat-resistant layer disposed on at least one side of the base film layer, wherein the heat-resistant layer comprises polymer particles; The mass ratio of the N element content to the C element content in the polymer particles is (2-10):
100.
2. The battery separator according to claim 1, characterized in that: The average particle size D50 of the polymer particles is 200-1000 nm, and the glass transition temperature Tg is above 150° C.
3. The battery separator according to claim 1 or 2, characterized in that: The polymer particles include rigid cyclic structural units, cross-linked monomer units and functional monomer units; in the polymer particles, the mass ratio of the rigid cyclic structural units, the cross-linked monomer units and the functional monomer units is (60-90): (5-15): (5-25).
4. The battery separator according to claim 3, characterized in that: The rigid cyclic structural unit is selected from one or more of aromatic vinyl compound monomer units, maleimide and its derivative monomer units, and vinyl carbazole compound monomer units; The cross-linking monomer unit is selected from one or more of a difunctional or multifunctional (meth) acrylate monomer unit, a difunctional or multifunctional allyl monomer unit, a difunctional or multifunctional acrylamide monomer unit, and a difunctional or multifunctional vinyl monomer unit; The functional monomer unit is selected from one or more monomer units containing an amine group.
5. The battery separator according to claim 1, characterized in that: The rigid cyclic structural unit is selected from one or more of styrene monomer units, methylstyrene monomer units, vinylnaphthalene monomer units, vinyltoluene monomer units, 2,4-dimethylstyrene monomer units, ethylstyrene monomer units, isopropylstyrene monomer units, tert-butylstyrene monomer units, butylstyrene monomer units, phenylstyrene monomer units, cyclohexylstyrene monomer units, benzylstyrene monomer units, isobornyl acrylate monomer units, isobornyl methacrylate monomer units, maleimide monomer units, C1-C12 alkyl-substituted maleimide monomer units, C6-C16 aryl-substituted maleimide monomer units, and vinylcarbazole; The cross-linking monomer unit is selected from the group consisting of ethylene glycol diacrylate monomer unit, polyethylene glycol diacrylate monomer unit, propylene glycol diacrylate monomer unit, dipropylene glycol diacrylate monomer unit, tripropylene glycol diacrylate monomer unit, trimethylolpropane triacrylate monomer unit, glycerol triacrylate monomer unit, pentaerythritol triacrylate monomer unit, polyethylene glycol dimethacrylate monomer unit, diethylene glycol dimethacrylate monomer unit, propylene glycol dimethacrylate monomer unit, dipropylene glycol dimethacrylate monomer unit, tripropylene glycol dimethacrylate monomer unit, One or more of the following monomer units: trimethylolpropane trimethacrylate monomer unit, trimethylolpropane trimethacrylate monomer unit, glycerol trimethacrylate monomer unit, pentaerythritol trimethacrylate monomer unit, divinylbenzene monomer unit, diallyl phthalate monomer unit, glycerol diallyl ether monomer unit, pentaerythritol diallyl ether monomer unit, pentaerythritol triallyl ether monomer unit, diallyl adipate monomer unit, N,N-methylenebisacrylamide monomer unit, acrylic acid allyl ether monomer unit, methacrylic acid allyl ether monomer unit, and divinylbenzene monomer unit; The functional monomer unit is selected from one or more of N-(2-aminoethyl)acrylamide monomer unit, N-(2-aminoethyl)methacrylamide monomer unit, N-(2-aminohexyl)acrylamide monomer unit, N-(2-aminohexyl)acrylamide monomer unit, 2-(tert-butylamino)ethyl methacrylate monomer unit, dimethylaminoethyl acrylate monomer unit, dimethylaminoethyl methacrylate monomer unit, acrylamide monomer unit, methacrylamide monomer unit, N-tert-butylacrylamide monomer unit, N-isopropylacrylamide monomer unit, N,N-dimethylacrylamide monomer unit, and N,N-diethylacrylamide monomer unit.
6. The battery separator according to claim 1, characterized in that: The thickness of the heat-resistant layer is 1-4 μm.
7. The battery separator according to claim 1, characterized in that: The heat-resistant layer also includes a binder and optionally a thickener and a wetting agent.
8. The battery separator according to claim 1, characterized in that: In the heat-resistant layer, the mass ratio of polymer particles, binder, thickener and wetting agent is 100:(3-10):(0.5-5):(0.5-3).
9. The battery separator according to claim 1, characterized in that: The base film layer is a polyolefin base film, and the polyolefin base film is selected from any one of a polyethylene porous film, a polypropylene porous film, a polypropylene / polyethylene / polypropylene three-layer composite porous film, and a polybutylene porous film.
10. A battery, characterized in that: A battery separator comprising the battery separator according to any one of claims 1 to 9.
Citation Information
Patent Citations
Lithium ion battery separation membrane and preparation method thereof, and lithium ion battery
CN107799696A
Polymer diaphragm, preparation method thereof, dispersoid, lithium ion battery and preparation method of lithium ion battery
CN110323391A
Lithium ion battery diaphragm and lithium ion battery
CN111682149A
Diaphragm slurry composition, composite ceramic diaphragm and secondary battery
CN118738765A
Non-aqueous electrolyte battery separator and lithium secondary battery
JP2000030686A
Cited By
Lyophilic polyolefin master batch as well as preparation method and application thereof
CN121086404A